Macroeconomic convergence in the West African monetary zone: Evidence from rank tests - Gyamfi, Emmanuel Numapau; Adam, Anokye Mohammed; Appiah, Emily Frimpomaa (Economics and Business Letters, 2019)
This article examined convergence of inflation and exchange rates in six (6) West African countries that make up the West African Monetary Zone (WAMZ). A non-parametric rank and score test was employed in the analysis. The results show that inflation and nominal exchange rates of Gambia, Ghana, Guinea, Liberia, Nigeria and Sierra Leone are converging. The findings have practical implications.